Improved Sequential Fusion of Heart-signal and Fingerprint for Anti-spoofing - N, Radha; N, Kavya; AC, Harsha (International Journal of Computer Sciences and Engineering, 2025)
Biometrics is one of the most encouraging authentication systems in the recent years. However, spoof attack is one of the main problems with a biometric system. Spoof attack falls within a subset of what is called presentation attack. The heart is an emerging biometric modality which is getting attention for its robustness against presentation attacks. Introducing heartsignal into a fingerprint biometric system can yield promising results showing its robustness against spoof attacks with increasing the authentication accuracy. In this work, a sequential fusion method is improved for anti-spoofing capability. The idea behind the proposed system is the utilization of the natural liveness property of heart-biometrics in addition to boosting the heart-signal scores to increase the anti-spoofing of a multimodal biometric system. We have evaluated our proposed method with public databases of fingerprint biometric and heart-signal (ECG signal). The obtained results are very encouraging for the development of a robust anti-spoofing multimodal authentication system.